Crime Of Corruption Of Village Funds Committed By Geuchik Gampong Paya Lipah Bireuen Regency Aceh (ANALYSIS OF DECISION NUMBER: 44/PID.SUS-TPK/2021/PN.BNA) - Nasril Rachmad; Yasmirah Mandasari Saragih (Yayasan Multidimensi Kreatif, 2024)
Law enforcement must consider three main elements: legal certainty, utility, and justice. Criminal law aims to achieve justice in society by resolving criminal cases and protecting human rights. However, the process often ends with punishing the perpetrator without adequately addressing the victim's physical and psychological losses. The Indonesian Police have adopted strategic policies to implement restorative justice, as outlined in Police Regulation Number 6 of 2019 and Circular Letter Number SE/8/VII/2018. This approach aims to restore victims to their original state as much as possible, fulfilling their interests and sense of justice. In Aceh, customary institutions are empowered to resolve community issues within their jurisdiction, supported by a Joint Decree and Qanun Aceh Number 9 of 2008, which regulate the resolution of minor offenses through customary courts. These courts, led by local leaders such as Keuchik, Tuha Peut, and Imeum Meunasah, work to resolve disputes peacefully and maintain community harmony. This study, titled